Cortical excitability on sleep deprivation measured by transcranial magnetic stimulation: A systematic review and meta-analysis - Yihui Zhang; Yuan Shi; Ye Zhang; Jian Jiao; Xiangdong Tang (Brain Research Bulletin)
Sleep deprivation is a common public problem, and researchers speculated its neurophysiological mechanisms related to cortical excitatory and inhibitory activity. Recently, transcranial magnetic stimulation combined with electromyography (TMS-EMG) and electroencephalography (TMS-EEG) have been used to assess cortical excitability in sleep-deprived individuals, but the results were inconsistent. Therefore, we conducted a meta-analysis to summarize relevant TMS-evoked indices of excitability and inhibition for exploring the cortical effects of sleep deprivation. In TMS-EMG studies, short-interval cortical inhibition (SICI) significantly decreased in sleep-deprived subjects; while the intracortical facilitation (ICF), resting motor threshold (RMT), and cortical silent period (CSP) were not significant compared to healthy controls. In TMS-EEG studies, the amplitude and slope of TMS-evoked potential (TEP) increased in sleep-deprived subjects. This study indicated that cortical inhibition decreased following sleep deprivation based on the TMS-EMG results and cortical excitability enhanced in the TMS-EEG results, supporting the disturbance of cortical excitability in sleep-deprived individuals.